Analisis Kinerja Keamanan Penerbangan Pada Unit Aviation Security di Bandar Udara Komodo Labuan Bajo - Hardiyati; Walid Jumlad (PT FORMOSA CENDEKIA GLOBAL, 2022)
Aviation Security Unit (AVSEC), plays an important role in supporting aviation security in this regard. Aviation safety disturbances such as passengers with sharp objects, alcohol, and lighters that endanger flight safety. The approach used is qualitative. Primary data sources from interviews with five sources using triangulation reliability test. Secondary data in the form of documents, books, journals and regulations as complementary and complementary data for writing this research. The results of the investigation show that AVSEC officers have the ability (skill, attitude, knowledge) to carry out security missions to ensure flight safety and security. AVSEC's performance at Labuan Bajo Airport complies with AVSEC's performance regulations and SOPs for the 3 Shift system.